Diazadiboraacenes: Synthesis, Spectroscopy and Computations. (2nd March 2023) - Ruhl, Julia; Oberhof, Nils; Dreuw, Andreas; Wegner, Hermann A.
Abstract: The incorporation of heteroatoms into hydrocarbon compounds greatly expands the chemical space of molecular materials. In this context, B−N doping takes a center stage due to its isosterism with a C=C‐bond. Herein, we present a new and modular synthetic concept to access novel diazadiborabenzo[ b ]triphenylenes 7 a–h using the B−N doped biradical 16 as intermediate. Characterization of the photophysical properties revealed the emission spectra of the diazadibora benzo[ b ]triphenylenes 7 a–h can conveniently be tuned by small changes of the substitution on the boron‐atom. All of the diazadibora compounds show a short life‐time phosphorescence. Additionally, we were able to rationalize the excited‐state relaxation of the diazadiboraacene 7 a via intersystem crossing by quantum chemical calculations. The new synthetic strategy provides an elegant route to various novel B−N doped acenes with great potential for applications in molecular materials. Abstract : The synthesis of a series of diazadiborabenzo[ b ]triphenylenes as novel B, N‐acenes via a stable biradical is presented. Characterization of their photophysical properties revealed that the emission spectra can conveniently be tuned by small changes of the substitution on the boron atom. In addition, short‐lived phosphorescence has been demonstrated.